2013
DOI: 10.1002/bmc.2963
|View full text |Cite
|
Sign up to set email alerts
|

An online coupled peritoneal macrophage/cell membrane chromatography and high‐performance liquid chromatography/mass spectrometry method to screen for anti‐inflammatory components from the Chinese traditional medicine Chloranthus multistachys Pei

Abstract: Cell membrane chromatography (CMC) is a chromatographic biological affinity method that uses specific cell membranes as the stationary phase. In this study, a novel peritoneal macrophage/cell membrane chromatography (PM/CMC)-online-high performance liquid chromatography/mass spectrometry (HPLC/MS) method was established to screen for the anti-inflammatory components from traditional Chinese medicines using hydrocortisone and dexamethasone as standards. The stationary phase of the CMC employed mouse peritoneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Cells membrane chromatography (CMC), a chromatographic biological affinity method that uses specific cell membranes as the stationary phase, has been confirmed as a simple, specific, effective screening method based on the binding principle that the recognition and interaction of drug molecules and targets, receptors, channels on the cell membrane [ 14 ]. A novel peritoneal macrophage/cell membrane chromatography (PM/CMC)-HPLC/MS method was shown to be an effective screening system for the rapid detection, enrichment, and identification of anti-inflammatory components from TCM [ 14 ]. Herein, we carried out this effective screening method to screen anti-inflammatory components from CB.…”
Section: Discussionmentioning
confidence: 99%
“…Cells membrane chromatography (CMC), a chromatographic biological affinity method that uses specific cell membranes as the stationary phase, has been confirmed as a simple, specific, effective screening method based on the binding principle that the recognition and interaction of drug molecules and targets, receptors, channels on the cell membrane [ 14 ]. A novel peritoneal macrophage/cell membrane chromatography (PM/CMC)-HPLC/MS method was shown to be an effective screening system for the rapid detection, enrichment, and identification of anti-inflammatory components from TCM [ 14 ]. Herein, we carried out this effective screening method to screen anti-inflammatory components from CB.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, increasing research has begun to explore CMC made of different cell membrane target receptors and coupled with GC–MS or HPLC–MS techniques to achieve high throughput screening. CMC of fibroblast growth factor receptor 4 (FGFR4), 80 epidermal growth factor receptor (EGFR), 81 α 1A receptors 82 and peritoneal macrophages (PMs) 83 have been coupled with other chromatographic techniques to screen a wider range of pharmacologically active components.…”
Section: Application Of 2d Chromatography In Screening Of Bioactive C...mentioning
confidence: 99%
“…Furthermore, mouse leukaemic monocyte macrophage cell line (RAW264.7) was usually used for the development of inflammatory model for studying of anti‐inflammatory drugs . In addition, mouse peritoneal macrophages have been used in bio‐membrane chromatography for screening potential active compounds from complex matrix . However, few studies about the interaction between macrophages and small molecules have been reported.…”
Section: Related Data In Face For Calculating Stoichiometry and Bindimentioning
confidence: 99%